Abraham Maslow's concept of education - Paweł Zieliński (Studia z Teorii Wychowania)
The author reconstructs Maslow's pedagogical thought, referring to hermeneutic and comparative research. The research relied on the final versions of Maslow's works capturing his theory of human development and education. The ideal of raising a good, altruistic person is realized in permanent education. Education and self-education are based on B-values, and the key here is the value of self-transcendence. The realization of this and other self-realization values requires the formation of a person with an inner sense of control and upbringing and schools that educate people holistically. The author also presents the influence of Maslow's theory on the development of pedagogical theory and practice.